Revealing the Introduction History and Phylogenetic Relationships of Passiflora foetida sensu lato in Australia - Hopley, Tara; Webber, Bruce L.; Raghu, S.; Morin, Louise; Byrne, Margaret (Frontiers in Plant Science, 2021)
Genomic analysis can be a valuable tool to assist management of non-native invasive species, through determining source and number of introductions as well as clarifying phylogenetic relationships. Here, we used whole chloroplast sequencing to investigate the introduction history of Passiflora foetida sensu lato in Australia and clarify its relationship with other Passiflora species present. Phylogenetic analysis of chloroplast genome data identified three separate genetic lineages of P. foetida s. l. present in Australia, indicating multiple introductions. These lineages had affinities to samples from three separate areas within the native range in Central and South America that represented phylogenetically distinct lineages. These results provide a basis for a targeted search of the native range of P. foetida s. l. for candidate biological control agents that have co-evolved with this species and are thus better adapted to the lineages that are present in Australia. Results also indicated that the Passiflora species native to Australia are in a separate clade to that of P. foetida s. l. and other introduced Passiflora species cultivated in Australia. This knowledge is important to assess the likelihood of finding biological control agents for P. foetida s. l. that will be sufficiently host-specific for introduction in Australia. As P. foetida s. l. is a widespread non-native invasive species across many regions of the world, outcomes from this work highlight the importance of first evaluating the specific entities present in a country before the initiation of a biological control program.